Unraveling the roles of Atg4 proteases from autophagy modulation to targeted cancer therapy. Issue 1 (1st April 2016) - Zhang, Lan; Li, Jingjing; Ouyang, Liang; Liu, Bo; Cheng, Yan
Highlights: We focus on the roles of the human Atg4 family in the LC3 conjugation system and their function in apoptosis. We discuss the roles of Atg4 proteases in several types of cancer. We demonstrate the development of Atg4 and its targeted candidate drugs in cancer. We further explore the roles of human Atg4 proteases as potential novel targets for cancer therapy. Abstract: Atg4 proteases are cysteine proteases, which are well known for their crucial roles in the lipidation and delipidation of LC3 during the autophagy process. At least four human Atg4 homologs have been reported according to their sequence homology to the yeast Saccharomyces cerevisiae (Sc) Atg4. Accumulating evidence has recently indicated that abnormal expression levels of some human Atg4 proteins occur in several types of cancer cells, which may be closely related to tumor progression, tumor suppression and cancer therapy resistance. In this review, we focus on highlighting the pivotal roles of the human Atg4 proteases in the LC3 conjugation system and their major function in autophagy. Moreover, we further explore the roles of human Atg4 proteases as potential novel targets for cancer therapy. Taken together, these findings would shed light on elucidating the key roles of Atg4 proteases from autophagy modulation to targeted cancer therapy.